50 Years of Real Convergence – Without Extractives Dependency and Tax Havens - Csoma, Róbert (Public Finance Quarterly, 2021)
In the world economy real convergence cannot be detected in the long term and lack of convergence is discussed in this article. The analysis is based on results and debates of economic growth theory and development studies. Special focus is placed on extractives dependent and tax haven countries and the article concludes that these countries considerably contribute to the partial real convergence process, limited only to some regions of the world economy. This paper also studies some common criteria of the catching-up process of emerging countries to developed economies. It concludes that although the factors of catching-up can be very unique in countries at different levels of development, yet there are some factors without which catching-up is hardly feasible nowadays in any country.